The Effect of Brand Awareness, Customer Engagement and Marketing Channel on Purchase Interest in Wedding Organizer Promises - Kiki Prasetya, Kiki Prasetya; Nurmingsih, Nurmingsih; Bachtar Bakrie, Bachtar Bakrie (LPPM Universitas Respati Indonesia, 2023)
Janji Nikah Wedding Organizer is a wedding organizer, which serves consumers who want to hold traditional and non-traditional wedding ceremonies. This study aims to determine the effect on the variables of brand awareness, customer engagement and marketing channels for buying interest. This research is an analytical survey with a quantitative approach, cross-sectional design. The data were collected through filling out a questionnaire using a total sampling technique, a population of 120 people as respondents. Analysis of the data used in this study is SEM-PLS (Partial Least Square). The results of this study indicate that several of the tested hypotheses gave positive and negative results, positive hypotheses were found in the customer engagement variable and marketing channels. While the results of the negative hypothesis are found in the brand awareness variable, partially this hypothesis has an effect and some does not affect Purchase Interest. The conclusion of this study is that each variable has its own influence, there is a negative and positive influence. Suggestions from this research on the Promise of Marriage Wedding Organizer, Brand awareness is not the only thing that can increase buying interest, but awareness of a brand also remains important to build trust in a brand, the company is expected to pay more attention to input and suggestions from consumers so that they are better known by the general public and increase buying interest. Keywords: Purchase intention, brand awareness, customer engagement, marketing channels.